Genomic characterization and evolutionary analysis of a Getah virus variant from piglets in central China - Guo, Zhenhua; Jiang, Yao; Li, Peng; Zhang, Gaiping (Frontiers in Microbiology, 2025)
IntroductionAs a re-emerging mosquito-borne virus, Getah virus (GETV) has been found in more than 10 countries surrounded by the Pacific Ocean and shows a broadly host tropism, raising concerns for the potential risk to public health. Horses and pigs are susceptible to GETV and play pivotal roles to the GETV adaptive evolution.MethodsHere, we reported a GETV outbreak in a pig farm with 20% suckling piglets losses. The genomic characteristics and evolutionary relationship of the pathogenic viral strain were also analyzed.ResultsThe isolate GETV-HeN202309 shared the highest nucleotide identity of 99.8% with strains from Guangdong and Sichuan province, suggesting it is an imported transmission. Although the phylogenetic analysis divided GETV into four groups (groups I–IV), only strains in group III were dominant and widely circulating in the fields. Furthermore, several amino acid substitutions in E2 protein were identified among different GETV groups and the substitution at D262th N site led to an additional glycosylation modification. Besides, six amino acid sites were under positive selection of E2 protein. Most of these special sites were distributed in domain A, B, and C of E2 protein, which are usually associated with the GETV infection and immune response.DiscussionOur study expands knowledge of GETV pathogenicity and deepens understanding of GETV genetic and adaptive evolution, which would be valuable for the development of diagnosis and prevention for GETV.